2007
DOI: 10.1590/s0102-311x2007000100024
|View full text |Cite
|
Sign up to set email alerts
|

Homens adolescentes e vida sexual: heterogeneidades nas motivações que cercam a iniciação sexual

Abstract: IntroduçãoUm olhar mais aprofundado sobre a AIDS indica que há participação intensa de homens jovens na dinâmica da epidemia. Paradoxalmente, a despeito de tal fato, esse grupo encontra-se praticamente à margem de uma atenção adequada no âmbito do Sistema Único de Saúde (SUS). De um modo geral, verifica-se que as ações realizadas no nível da atenção básica voltam-se à distribuição esporádica de preservativos masculinos por unidades básicas de saúde, podendo-se afirmar que tal abordagem não considera, com propr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
1
3
0
7
Order By: Relevance
“…Also, it is possible to see that behaviors and feelings varied in intensity and complexity in this period of life, as indicated by the items of the RHS, which ranged from simple to more complex behaviors, such as being in love and telling someone that you love them. These findings agree with studies carried out with Brazilian samples, which indicate that the first affective-romantic manifestations and the first pre-sexual experiences occur predominantly before the age of 15 (Borges & Schor, 2007;Heilborn et al, 2008). Other Brazilian studies indicate that the beginning of sexual practice in adolescence, a direct consequence of romantic interest and pre-sexual experiences, would occur between 14 and 17 years of age (Santos, Albuquerque, Bandeira, & Colares, 2015), corroborating the idea that romantic interest and involvement would be part of a developmental sequence that would culminate in the sexual relationship of adolescents.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Also, it is possible to see that behaviors and feelings varied in intensity and complexity in this period of life, as indicated by the items of the RHS, which ranged from simple to more complex behaviors, such as being in love and telling someone that you love them. These findings agree with studies carried out with Brazilian samples, which indicate that the first affective-romantic manifestations and the first pre-sexual experiences occur predominantly before the age of 15 (Borges & Schor, 2007;Heilborn et al, 2008). Other Brazilian studies indicate that the beginning of sexual practice in adolescence, a direct consequence of romantic interest and pre-sexual experiences, would occur between 14 and 17 years of age (Santos, Albuquerque, Bandeira, & Colares, 2015), corroborating the idea that romantic interest and involvement would be part of a developmental sequence that would culminate in the sexual relationship of adolescents.…”
Section: Resultssupporting
confidence: 91%
“…For example, a study by Borges and Schor (2007), conducted with male participants only, aged 15 to 19 years, in the city of São Paulo, showed the mean age of the first kiss, first date and first sexual intercourse as being, respectively, 11.5 years, 13.2 years and 14.9 years. Heilborn et al (2008), based on a multicenter study with more than 200 participants, indicated 15 years as the age of first dating, with sexual initiation at around 16 years for adolescents of both sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the adopted preventive practices basically consist in the distribution of preservatives, which is not fully efficient, and that further research on sexual and reproductive health of these people is needed (2) .Over In terms of economic status, 11 (42.3%)reported family income lower than one minimum wage; nine (34.6%) between one and two minimum wages; four (15.4%) reported three minimum wages and two (7.7 %) reported an income of four minimum wages.Regarding the number of children, the study shows that 14 (53.8%) parents have one to two children; nine (34.6%) have three to four children, and three (11.6%) have five children. The distribution of children regarding gender was balanced; parents of 69 adolescents (100%) were interviewed, 39…”
mentioning
confidence: 99%
“…Studies show that the adopted preventive practices basically consist in the distribution of preservatives, which is not fully efficient, and that further research on sexual and reproductive health of these people is needed (2) .…”
mentioning
confidence: 99%
“…A diferença da iniciação sexual entre homens e mulheres pode ser entendida mais por razões de gênero do que por questões biológicas do sexo. Isso porque, para homens, o sexo é apresentado desde cedo como algo certo e, para as meninas, como algo errado, por isso eles seriam mais estimulados a se iniciarem mais cedo do que as mulheres, o que resulta em diversos estudos encontrando uma prevalência na iniciação sexual de homens ocorrendo mais precocemente do que em mulheres 11,12,20,21,23,41,43 .Segundo o IBGE, nas capitais e no Distrito Federal a frequência de adolescentes escolares no 9º ano do ensino fundamental, do sexo masculino, que tiveram relação sexual, foi de 43,7%; do sexo feminino, a proporção foi de 18,7% 27 .Os motivos para essa iniciação sexual precoce em adolescentes do sexo masculino são diversos. Estudos com essa temática norteiam que, dentre os vários motivos destacam-se a baixa escolaridade, estrutura familiar, trabalho, grupos sociais, gênero, autoafirmação da identidade, entre outros 12,13,44,45 .…”
unclassified